2010
DOI: 10.1002/masy.201051065
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Investigation of UHMWPE Oxidation Submitted to Accelerated Aging Procedure

Abstract: Summary: In the present study, an accelerated ageing by oxidative degradation of UHMWPE in hydrogen peroxide solution was performed and the inhibition with ascorbic acid (vitamin C) was analyzed. Both systems were extensively characterized by Fourier Transformed Infrared Spectroscopy (FTIR). Different chemical groups of UHMWPE associated with the degradation reaction were monitored for over 120 days in order to evaluate the possible oxidation mechanisms involved and the inhibitory behavior of vitamin C. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Studies have shown that polyethylene wear patterns in articial joint replacements are not always identical and cannot be explained exclusively by mechanical factors, such as the weight and degree of physical activity of the patients. [115][116][117] In cases of premature and excessive wear of polyethylene bearings, chemical degradation and oxidation of the polymer can signicantly lower its mechanical resistance and result in an accelerated wear-off process. 118,119 Polymer oxidation, which results in the embrittlement of the prosthetic material, can generate wear debris that eventually triggers an immune response and subsequent implant loosening (Fig.…”
Section: Oncology: Tumor Treatment and Magnetic Hyperthermiamentioning
confidence: 99%
“…Studies have shown that polyethylene wear patterns in articial joint replacements are not always identical and cannot be explained exclusively by mechanical factors, such as the weight and degree of physical activity of the patients. [115][116][117] In cases of premature and excessive wear of polyethylene bearings, chemical degradation and oxidation of the polymer can signicantly lower its mechanical resistance and result in an accelerated wear-off process. 118,119 Polymer oxidation, which results in the embrittlement of the prosthetic material, can generate wear debris that eventually triggers an immune response and subsequent implant loosening (Fig.…”
Section: Oncology: Tumor Treatment and Magnetic Hyperthermiamentioning
confidence: 99%
“…It has been shown that subjecting PE to mild oxidative conditions produces oxygen-containing low molecular mass degradation products on the surface of the substrate, mainly mono- and dicarboxylic acids, along with gaseous products, depending on the conditions during the degradation. Oxidation can take place in air or in water and is facilitated by oxidizing chemicals, such as nitric acid and hydrogen peroxide, in combination with an elevated temperature or UV light. Due to its energetically favorable transition state, succinic acid is often the most abundant product formed during decomposition …”
Section: Introductionmentioning
confidence: 99%
“…This oxidation reaction is "automatic", known as "automatic oxidation". 19,20 It is generally relatively slow and can be promoted by many factors such as heat. Heat can force oxygen to penetrate into the interior from the exterior of the polymer.…”
Section: Surface Topographymentioning
confidence: 99%